Finance and Development, September 1969. (Finance and Development; Finance and Development, 1969)
This paper discusses infrastructure development and building of roads in Honduras. The paper highlights that in countries with backward transportation systems, the concept of 'road' takes on an almost philosophical significance. The paper discusses the Western Highway in Honduras that was financed in 1961 by the first credit ever made by the International Development Association, the World Bank's soft-loan affiliate. Between its terminal points, the highway provides individuals of the area with reasonably easy access to markets, and is encouraging them to expand their agricultural production.